Discovery of an Accretion Streamer and a Slow Wide-Angle Outflow Around Fu Orionis - Perez-Marquez, S; Weber, P (Institute of Physics, 2024)
We present Atacama Large Millimeter/submillimeter Array 12-m, 7-m, and Total Power Array observations of the FU Orionis outbursting system, covering spatial scales ranging from 160 to 25,000 au. The high-resolution interferometric data reveal an elongated 12CO(2-1) feature previously observed at lower resolution in 12CO(3-2). Kinematic modeling indicates that this feature can be interpreted as an accretion streamer feeding the binary system. The mass infall rate provided by the streamer is significantly lower than the typical stellar accretion rates (even in quiescent states), suggesting that this streamer alone is not massive enough to sustain the enhanced accretion rates characteristic of the outbursting class prototype. The observed streamer may not be directly linked to the current outburst, but rather a remnant of a previous, more massive streamer that may have contributed enough to the disk mass to render it unstable and trigger the FU Orionis outburst. The new data detect, for the first time, a vast, slow-moving carbon monoxide molecular outflow emerging from this object. To accurately assess the outflow properties (mass, momentum, and kinetic energy), we employ 13CO(2-1) data to correct for optical depth effects. The analysis indicates that the outflow corresponds to swept-up material not associated with the current outburst, similar to the slow molecular outflows observed around other FUor and Class I protostellar objects. © 2024. The Author(s). Published by the American Astronomical Society.